Current Status of Pediatric Labeling in China and the near Future Efforts Needed for the Country - Li, Zhiping; Wang, Yi; Wu, Dan; Gao, Xuan; Wang, Zhiyun (Frontiers in Pediatrics, 2014)
Background: Children are recognized as “therapeutic orphan” in many parts of the world, one expression of this is the lack of adequate pediatric labeling information. Some researches have been done to investigate the pediatric labeling condition in the U.S. and other countries, but no national studies had been carried out in China. This survey was conducted aiming to inquire the current situation of pediatric labeling in China. Methods: We investigated 6020 child-applied medicines from 15 representative Chinese hospitals, and analyzed the information according to the dosage forms, therapeutic category, and label information integrity. Results: Among all these medicines, only 238 (3.95%) are pediatric products, the rest are adult formulations with an extended use in children. The major pediatric formulations were injection (45.95%), tablet (23.69%) and capsule (4.93%), respectively. Alimentary tract/ metabolism medicine (24.70%) and infections medicines (20.60%) had the most species . In prescription drugs, only 210 of 5187 (4%) medicines had adequate pediatric labeling information. The main cause of this deficiency was lack of evidence derived from pediatric clinical trials. Conclusion: The dilemma of “therapeutic orphan” requires significant attention. Inadequate labeling information and lack of pediatric clinical trials were two prominent issues in China. It calls for more efforts from pharmaceutical industries, regulatory agencies, and legislature in China to collaborate and find solution to improve the situation.